A 12-Month Open-Label Extension Study of the Safety and Tolerability of Lisdexamfetamine Dimesylate for Major Depressive Disorder in Adults. Issue 4 (August 2018) - Richards, Cynthia; Iosifescu, Dan V.; Mago, Rajnish; Sarkis, Elias; Geibel, Brooke; Dauphin, Matthew; McIntyre, Roger S.; Weisler, Richard; Brawman-Mintzer, Olga; Gu, Joan; Madhoo, Manisha
Abstract: Purpose/Background: Psychostimulant augmentation is considered a potential treatment strategy for individuals with major depressive disorder who do not adequately respond to antidepressant monotherapy. The primary objective of this 12-month open-label extension study was to evaluate the safety and tolerability of lisdexamfetamine dimesylate (LDX) as augmentation therapy to an antidepressant in adults with major depressive disorder. Methods/Procedures: Eligible adults who completed 1 of 3 short-term antecedent LDX augmentation of antidepressant monotherapy studies were treated with dose-optimized LDX (20–70 mg) for up to 52 weeks while continuing on the index antidepressant (escitalopram, sertraline, venlafaxine extended-release, or duloxetine) assigned during the antecedent short-term studies. Safety and tolerability assessments included the occurrence of treatment-emergent adverse events and vital sign changes. Findings/Results: All 3 antecedent studies failed to meet the prespecified primary efficacy endpoint, so this open-label study was terminated early. Headache (15.5% [241/1559]), dry mouth (13.6% [212/1559]), insomnia (13.1% [204/1559]), and decreased appetite (12.1% [189/1559]) were the most frequently reported treatment-emergent adverse events. The greatest mean ± SD increases observed for systolic and diastolic blood pressure and for pulse were 2.6 ± 10.85 and 1.7 ± 7.94 mm Hg and 6.9 ± 10.27 bpm, respectively. Monitoring determined that less than 1% of participants experienced potentially clinically important changes in systolic blood pressure (10 [0.6%]), diastolic blood pressure (8 [0.5%]), or pulse (6 [0.4%]). Implications/Conclusions: The overall safety and tolerability of long-term LDX augmentation of antidepressant monotherapy was consistent with the profiles of the short-term antecedent studies, with no evidence of new safety signals. Abstract : Supplemental digital content is available in the text.